A Network Pharmacology of Brotowali (Tinospora cordifolia) on Immunity Cases - Susanto, Awang Farhan Ferdyan Syah; Jamil, Ahmad Shobrun; Muchlisin, M Artabah; Almuhtarihan, Irsan Fahmi (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 3 (2023): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v3i0.2469, 2023)
COVID-19 is a disease outbreak related to the human immune system. The process of spreading very quickly makes this outbreak a dangerous pandemic. COVID-19 cases in 2020 in Indonesia, positive cases were reaching 1,089,308 people with a death rate of 20,277 people as of 2 February 2021. Efforts are being made to reduce and prevent virus transmission by boosting the immune system using an immunomodulator. Based on the literature studies that have been conducted, several Indonesian local plants have potential as immunomodulator. The in silico test was carried out because the computer simulation method has scientific validity, is relatively new, and has a high level of accuracy. This study aims to determine the protein network associated with the body's immune system, which is activated due to the administration of Brotowali (Tinospora Cordifolia) . The research method used is exploratory descriptive with in silico analysis using a computational model with online databases, including KNApSAck, Dr. Duke, Pubchem, SwissADME, SwissTargetPrediction, Venny, StringDB, and KEGG. Based on the results of pharmacological network analysis , T. Cordifolia contains 33 secondary metabolites, 25 of which have high bioavailability. Proteins associated with T. cordifolia contain 640 compounds, and those related to immunomodulators contain 1380 proteins. The intersection results obtained 191 proteins predicted to interact with T. cordifolia and are related to immunomodulators. Based on KEGG Pathway analysis, there are five critical pathways in the immunomodulatory system, namely Th17 cell differentiation, IL-17 signaling pathway, T cell receptor signaling pathway, Fc epsilon RI signaling pathway, and TNF signaling pathway. 1-hydroxy-2-methyl-anthraquinone can be an immunomodulator because it interacts with five critical pathways in the immunomodulator system.